P210bcr‐abl induces amoeboid motility by recruiting ADF/destrin through RhoA/ROCK1. Issue 1 (9th October 2012) - Rochelle, Tristan; Daubon, Thomas; Van Troys, Marleen; Harnois, Thomas; Waterschoot, Davy; Ampe, Christophe; Roy, Lydia; Bourmeyster, Nicolas; Constantin, Bruno
Abstract : We previously demonstrated that the Bcr‐Abl oncogene, p210 bcr‐abl, through its unique GEF domain, specifically activates RhoA and induces spontaneous amoeboid motility. We intend to study the pathways downstream RhoA controlling amoeboid motility. Mouse prolymphoblastic cells (Ba/F3 cell line) expressing different forms of Bcr‐Abl were embedded in 3‐dimensional (3D) Matrigel to study motility and explore the effects of inhibiting Rho pathway (inhibitors and siRNAs). The phosphorylation levels of cofilin‐1 and destrin were analyzed by 2‐dimensional electrophoresis. Composition of Bcr‐Abl signalplex in different conditions was determined by coimmunoprecipitation. Ba/F3p190 and Ba/F3 expressing a mutant form of p210 bcr‐abl (unable to activate RhoA) cells presented a spontaneous motility, but not an amoeboid type. p210 bcr‐abl ‐induced amoeboid motility in a 3D matrix requires isoform‐specific RhoA/ROCK‐1/destrin signaling. Next to the conventional Rho/ROCK/MLC/myosin pathway, this pathway is a crucial determinant for amoeboid motility, specific for the destrin isoform (and not its coexpressed homologue cofilin‐1). Also, the presence of destrin (and not cofilin‐1) in the p210 bcr‐abl complex is dependent on ROCK1, and this signalplex is required for amoeboid motility. This underscores isoform‐specific function within the ADF/cofilin family and provides new insight into Bcr‐Abl signaling to amoeboid motility and possible impact on understanding chronic myeloid leukemia progression.—Rochelle, T., Daubon, T., Van Troys, M., Harnois, T., Waterschoot, D., Ampe, C., Roy, L., Bourmeyster, N., Constantin, B. p210 bcr‐abl induces amoeboid motility by recruiting ADF/destrin through RhoA/ROCK1. FASEB J. 27, 123–134 (2013). www.fasebj.org